Botulinum neurotoxin type A-cleaved SNAP25 is confined to primary motor neurons and localized on the plasma membrane following intramuscular toxin injection. (3rd June 2017) - Cai, Brian B.; Francis, Joseph; Brin, Mitchell F.; Broide, Ron S.
Highlights: Antibody specific to botulinum toxin A-cleaved SNAP25 plus 3-dimensional imaging offer insights into toxin distribution. Botulinum toxin A injected in rat muscle results in SNAP25197 staining confined to related motor neurons in the spinal cord. A high toxin dose results in random SNAP25197 staining in distal muscles and spinal cord regions indicating systemic spread. No evidence was found for transcytosis in the spinal cord following intramuscular injection of botulinum toxin type A. At a high dose of toxin, SNAP25197 is colocalized with synaptic markers on the membrane of motor neurons in the spinal cord. Abstract: The mechanism of action of botulinum neurotoxin type A (BoNT/A) is well characterized, but some published evidence suggests the potential for neuronal retrograde transport and cell-to-cell transfer (transcytosis) under certain experimental conditions. The present study evaluated the potential for these processes using a highly selective antibody for the BoNT/A-cleaved substrate (SNAP25197 ) combined with 3-dimensional imaging. SNAP25197 was characterized in a rat motor neuron (MN) pathway following toxin intramuscular injections at various doses to determine whether SNAP25197 is confined to MNs or also found in neighboring cells or nerve fibers within spinal cord (SC). Results demonstrated that SNAP25197 immuno-reactive staining was colocalized with biomarkers for MNs, but not with markers for neighboring neurons, nerve fibers or glial cells. Additionally, a high dose of BoNT/A, but not a lower dose, resulted in sporadic SNAP25197 signal in distal muscles and associated SC regions without evidence for transcytosis, suggesting that the staining was due to systemic spread of the toxin. Despite this spread, functional effects were not detected in the distal muscles. Therefore, under the present experimental conditions, our results suggest that BoNT/A is confined to MNs and any evidence of distal activity is due to limited systemic spread of the toxin at higher doses and not through transcytosis within SC. Lastly, at higher doses of BoNT/A, SNAP25197 was expressed throughout MNs and colocalized with synaptic markers on the plasma membrane at 6 days post-treatment. These data support previous studies suggesting that SNAP25197 may be incorporated into SNARE-protein complexes within the affected MNs.